Guerra e política : Guilherme, o Conquistador e a Batalha de Hastings nas fontes anglo-normandas dos séculos XI e XII - Ferrarese, Lucio Carlos (2015)
This research aims to understand the military actions of William the Conqueror at the Battle of Hastings in 1066, as well as his military capabilities as political propaganda for the justification of his reign. From the analysis of anglo-norman relations in the eleventh century, we seek to understand the political and ideological motivations that led William to claim the throne of England and how he influenced the anglo-saxon thought for the maintenance of his power. We will discuss the performance of the Norman king and his army, the strategies and the "logistics" used during the battle, eand we debate the new military and social ideals that this king seeks to implement in England after his conquest. We will use as sources the Bayeux Tapestry, the Anglo-Saxon Chronicle, and the Chronicle of William of Poitiers. In addition to the sources, we will count as an analytical support with the works that discuss the historical context of the eleventh century England, as well as those relating to medieval wars and battles, especially those relating to the Battle of Hastings, such as: The Bayeux Tapestry and the Norman invasion (1973), by Lewis Thorpe; Hastings 1066 (1994), by Christopher Gravett; and The Oxford Illustrated History of Medieval England (1997), by Nigel Saul.